P2 receptors mRNA expression profiles in macrophages from ankylosing spondylitis patients and healthy individuals. (29th December 2019) - Akhtari, Maryam; Zargar, Seyed Jalal; Vojdanian, Mahdi; Ashraf‐Ganjouei, Amir; Javinani, Ali; Hamzeh, Elham; Rezaiemanesh, Alireza; Jamshidi, Ahmadreza; Mahmoudi, Mahdi
Abstract: Background: Ankylosing spondylitis (AS) is a multifactorial rheumatic disease which mainly involves the axial skeleton. Macrophages and extracellular nucleotides have been shown to contribute to the inflammation process in autoimmune diseases. Membrane‐bound purinergic P2 receptors might be involved in the modulation of immune cells in AS. Therefore, we aimed to analyze the messenger RNA (mRNA) expression of P2 receptors in the macrophages of AS patients and healthy controls. Methods: Twenty‐three AS patients and 23 age‐ and sex‐matched healthy individuals were included in our study. Whole blood‐separated monocytes of study participants were stimulated by macrophage colony‐stimulating factor for 7 days and differentiated to macrophages. Monocyte and macrophage markers were analyzed by flow cytometry. SYBR green real‐time polymerase chain reaction was used to measure the relative expression levels of P2RX1, P2RX2, P2RX3, P2RX4, P2RX5, P2RX6, P2RX7, P2RY1, P2RY2, P2RY4, P2RY6, P2RY11, P2RY12, P2RY13, P2RY14, and PANX1 genes. Results: P2RY13 and P2RY6 genes had the highest expression levels in macrophages among P2RY genes. P2RY1 mRNA expression was significantly down‐regulated (−1.75 fold) and P2RY14 was up‐regulated (2.6 fold) in macrophages of AS patients compared to healthy individuals. P2RX4 gene had the highest expression in monocyte‐derived macrophages, followed by P2RX7 and P2RX 1 genes. There was no significant difference in P2X receptor mRNA expression level between macrophages of AS patients and healthy individuals. Conclusions: Our results indicate that AS patients show altered expression levels of P2 receptor genes. Moreover, these changes might be associated with disease activity and patients' status.